The Application of Nanocoating and Cold-Dip Galvanization on Mitigating Corrosion for Ship and Offshore Mooring Chains - Orji, Charles U; Nitonye, Samson; Asuquo, Felix U (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Corrosion is a major challenge for marine vessels and offshore mooring systems due to the aggressive maritime environment characterized by high salinity, biological activity, and temperature variations. This study explores the effectiveness of nano-coatings derived from waste snail shells compared to traditional cold-dip galvanization in mitigating corrosion on ANSI A36 steel mooring chains. Three specimen groups—nano-epoxy composite coating, cold-dip galvanized, and bare metal—were tested in fresh and saltwater environments over a five-week period. Water composition, pH, and salinity were analyzed using Atomic Absorption Spectroscopy (AAS) to assess their influence on corrosion behavior. Weekly measurements of corrosion rates were taken to evaluate the protective performance of each treatment. The results demonstrated a significant reduction in corrosion rates for both nano-coated and galvanized samples compared to bare metal. Specifically, the nano-epoxy coating reduced corrosion from 0.13 mm/week to below 0.02 mm/week, while cold-dip galvanized samples showed a similar decline, converging around 0.02 mm/week. Bare metal, however, stabilized at approximately 0.05 mm/week. These findings suggest that nano-coatings are a promising, sustainable alternative to conventional galvanization, enhancing the durability and operational lifespan of mooring systems and offshore structures. This advancement supports the offshore industry’s need to meet stringent classification guidelines and extend the design life of critical components. Further long-term exposure studies are recommended to confirm the sustained effectiveness of nano-epoxy coatings in marine environments.